Coagulopathy as a Prodrome of Cytokine Storm in COVID-19-Infected Patients - Guo, Hui; Sheng, Ying; Li, Wei; Li, Fei; Xie, Zongyu; Li, Jing; Zhu, Yuhe; Geng, Jian; Liu, Gang; Wang, LeJian; Li, Jing; Wang, Fengchao (Frontiers in Medicine, 2020)
Background The rapid coronavirus disease 2019 (COVID-19) pandemic has hit hard on the world and causes panic since the virus causes serious respiratory infectious illness and easily leads to severe conditions such as immune system overactivation or cytokine storm. Due to the limited knowledge of this infectious course of this coronavirus and a lack of an effective treatment for this fatal disease, the mortality remains high. The emergence of cytokine storm in patients on severe condition has been reported as the top reason of the death of patients with COVID-19 infection. However, the causative mechanism of cytokine storm remains elusive. Thus, we aim to observe the association of coagulopathy (D-dimer) with cytokine (i.e. IL-6) and CT imaging in COVID-19 infected patients. Methods In this retrospective observational study, we systematically analyzed the comprehensive clinical laboratory data of COVID-19 positive patients in different illness groups of mild, moderate, severe conditions according to Chinese Clinical Guidance for COVID-19 Pneumonia Diagnosis and Treatment (7th edition). T tests and Chi-square tests were used for two-group comparisons. One-way ANOVA was used for three-group comparisons. Pearson and spearman correlation coefficients of the D-dimer level with IL-6 and CT imaging were computed at baseline. With regular liquid biopsy approach, D-dimer, IL-6, NLR was recorded repeatedly with time curve to investigate the disease progression, along with CT imaging, and other indicators. Results All the 64 patients were clinically evaluated and classified into three groups of mild (32 cases), moderate (23 cases), severe (9 cases). D-dimer level positively correlated with IL-6 (R=0.5) at the base line when COVID-19 infected patients were admitted. In addition, we observed that D-dimer rises early than cytokine storm represented by IL-6 surge, which suggests that coagulopathy might act as trigger to potentiate cytokines storm. Conclusion Integrated analysis revealed the positive correlation of coagulopathy with cytokine storm in COVID-19 infected patients, D-dimer rise early, which indicated coagulopathy act as a prodrome of cytokine storm. Coagulopathy can be used to monitor early cytokine storm in COVID-19 infected patients.